2018
DOI: 10.3389/fncel.2018.00390
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Cortical Activity in an Animal Model of Dystonia Caused by Cerebellar Dysfunction

Abstract: The synchronization of neuronal activity in the sensorimotor cortices is crucial for motor control and learning. This synchrony can be modulated by upstream activity in the cerebello-cortical network. However, many questions remain over the details of how the cerebral cortex and the cerebellum communicate. Therefore, our aim is to study the contribution of the cerebellum to oscillatory brain activity, in particular in the case of dystonia, a severely disabling motor disease associated with altered sensorimotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…Similarly to previous studies, we showed that a limited region of cerebellar dysfunction could induce isolated abnormal movements such as limb prolonged contraction that resemble focal dystonia (24). The kainate microinjections into the left cerebellar cortex induced, especially ipsilateral dystonic contractions, whereas vermis microinjections induced generalized dystonia (21). After repeated kainic acid application on the left cerebellar hemisphere, we found a significant reduction of the interhemispheric coherence in low-frequency bands (delta, theta, beta).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly to previous studies, we showed that a limited region of cerebellar dysfunction could induce isolated abnormal movements such as limb prolonged contraction that resemble focal dystonia (24). The kainate microinjections into the left cerebellar cortex induced, especially ipsilateral dystonic contractions, whereas vermis microinjections induced generalized dystonia (21). After repeated kainic acid application on the left cerebellar hemisphere, we found a significant reduction of the interhemispheric coherence in low-frequency bands (delta, theta, beta).…”
Section: Discussionsupporting
confidence: 87%
“…Therapeutic modulation of the cerebellum or its outflow pathway was occasionally found to be effective in the treatment of dystonia (19,20). In animal models, dystonia can be triggered by kainic acid (a glutamate receptor agonist) injection into the cerebellum surface (21)(22)(23). Raike et al showed that focal and generalized dystonia may have similar physiopathology and can be treated with similar strategies (24).…”
Section: Introductionmentioning
confidence: 99%
“…DN optogenetic θ-burst stimulations decreased the abnormal motor state in Gnal +/- mice following oxotremorine injection ( Figure 5H ). To confirm these observations, we also evaluated the activity of mice by measuring the percentage of time spent moving in an open field (‘active wakefulness’) ( Georgescu et al, 2018 ). In the saline-treated WT mice, DN optogenetic θ-burst stimulations had no significant effect on the active wake time.…”
Section: Resultsmentioning
confidence: 99%
“…Also, LFP oscillations could help in the coordination of spike timing even if cells are not rhythmic (Bush and Burgess, 2019 ), as we show here that a greater proportion of Golgi or Purkinje cell SSs are phase-locked than are outright rhythmic. Our study has focused on normal circuits, but oscillatory flow could also have implications in pathological circuits, influencing cerebellar and extra-cerebellar connectivity (Bares et al, 2010 ; Georgescu et al, 2018 ). As oscillations flowing through circuits can represent time (Buzsáki and Llinás, 2017 ), the understanding of oscillatory flow and the timing of unit activity through the cerebellar cortex, and outward, is of particular interest.…”
Section: Discussionmentioning
confidence: 99%